Conjugate Effects of Heat and Mass Transfer on Natural Convection Flow Across an Isothermal Horizontal Circular Cylinder With Chemical Reaction - Hye, Md. A. A.; Molla, Md. M. M.; Khan, M. A. H. A. H. (Nonlinear Analysis: Modelling and Control, 2007)
Natural convection flow across an isothermal cylinder immersed in a viscous incompressible fluid in the presence of species concentration and chemical reaction has been investigated. The governing boundary layer equations are transformed into a system of non-dimensional equations and the resulting nonlinear system of partial differential equations is reduced to a system of local non-similarity boundary layer equations, which is solved numerically by a very efficient implicit finite difference method together with the Keller-box scheme. Numerical results are presented by the velocity, temperature and species concentration profiles of the fluid as well as the local skin-friction coefficient, local heat transfer rate and local species concentration transfer rate for a wide range of chemical reaction parameter γ (γ = 0.0, 0.5, 1.0, 2.0, 4.0), buoyancy ratio parameter N (N = −1.0, −0.5, 0.0, 0.5, 1.0), Schmidt number Sc (Sc = 0.7, 10.0, 50.0, 100.0) andPrandtl number Pr (Pr = 0.7, 7.0).
Keywords: natural convection; chemical reaction; skin-friction; rate of heat transfer; rate of species concentration; cylinder